Особливості онтогенезу видів роду Grindelia Willd. - Klimenko, O.L.; Menshova, V.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The results of studying the ontogenesis of species of the genus Grindelia Willd. (G. robusta Nuttall, G. integrifolia DC, G. squarrosa (Pursh) Dunal.) in conditions of culture (ex situ) are represented.